Ebony and Ivory - Abu Bakar, Ainul Zakiah; Abdul Karim, Muhammad Shahrim; Mohd Ghazali, Hasanah (Universiti Putra Malaysia Press, 2015)
At a glance the title may remind you of the famous song. Interestingly, it is in fact describing a popular delicacy in the Asian region. You may not know the name of the chicken, but a description of this chicken may jog your memory. The unusual black-skinned and black-boned Silkie Chicken or scientifically known as Gallus gallus domesticus is named for its fluffy silk-like plumage that may range in colour from white, black, grey or gold.